Patriarchy Negotiation: Batak Women and the Domination of the Role of Cultural Space - Nasution, Ulfa Ramadhani (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2024)
This paper tries to understand how Angkola Batak women negotiate a patriarchal cultural system, by trying to find a middle way that still goes hand in hand with Batak customs and Islam, and on the other hand, slowly brings them out of the shadow of patriarchy itself. Through the results of interviews and field observations, this paper argues that the relationship between women and the patriarchal cultural system is dynamic in different structures and times. Women constantly use different ways to deal with the difficulties they face in different situations. This paper concludes that only by describing the dynamic negotiation context and the process can we avoid the assumption that Batak women are passive, oppressed, and powerless subjects. This paper describes the negotiations carried out by Angkola Batak women to achieve changes in gender relations with a more accommodating attitude towards inequality itself. Thus, the defense that emerges from women's actions is a framework that can change the patriarchal cultural order, no matter how slowly the change occurs. [Makalah ini mencoba memahami bagaimana perempuan Batak Angkola menegosiasikan sistem budaya patriarki, dengan upaya menemukan jalan tengah yang tetap beriringan dengan adat Batak dan agama Islam, dan di sisi lain secara perlahan mengeluarkan mereka dari bayang-bayang patriarki itu sendiri. Melalui hasil wawancara dan observasi lapangan, makalah ini berpendapat bahwa hubungan perempuan dengan sistem budaya patriarki berdinamika dalam struktur dan waktu yang berbeda. Perempuan secara terus-menerus menggunakan cara yang berbeda untuk mengatasi kesulitan yang mereka hadapi dalam situasi tertentu.Temuan dalam makalah ini adalah bahwa hanya dengan  menggambarkan konteks dan proses negosiasi yang dinamis tersebut maka dapat menghindari asumsi yang menyatakan bahwa perempuan Batak adalah subjek pasif, tertindas, dan tidak berdaya. Makalah ini menggambarkan perundingan yang perempuan Batak Angkola lakukan untuk mencapai perubahan relasi gender dengan sikap lebih akomodatif terhadap ketidaksetaraan itu sendiri. Maka bentuk pertahanan yang terlihat dari tindakan perempuan merupakan kerangka yang dapat merubah tatanan budaya patriarki tanpa peduli seberapa lambat perubahan itu akan terjadi.]